Financial policy reform - Reserve Bank of New Zealand; Reserve Bank of New Zealand (Wellington : Reserve Bank of New Zealand, 1986)
This book brings together in one volume a range of 13 articles reviewing recent financial policy reforms in New Zealand. It explains the background to, and rationale for, the changes in monetary policy and exchange rate policy that followed the change of Government in July 1984. The topics covered include the removal of the various controls on interest rates and foreign exchange movements, the abolition of statutory ratios over financial institutions and floating of the exchange rate etc.
includes index
includes bibliography pp.208-215
usc 29/06/2017
Loans
Keywords: Monetary policy; New Zealand